111 Creating a safe environment for young adults to achieve independent home haemodialysis. (December 2018) - Sinnott, K; Hothi, D
Abstract : Background: Some young adults may be suitable for home haemodialysis (HD) but lack of supervision or support may prevent this becoming a reality. Aims: We describe our enhanced safety approach which enabled a 17 year old with an arterio-venous fistula to transition from in-centre HD to home HD, independently. Results: When planning the possibility of a young adult dialysing independently at home a number of unique safety issues need to be considered and mitigated against in addition to addressing common concerns such as non-adherence to treatment. We individualised the training programme, modifying the standard teaching to incorporate additional safety measures focusing on a heightened awareness and earlier recognition of potential complications. Technology such as medical alarm necklaces and watches, alarm amplifiers and blood leak detectors alerted the young adult or the local medical emergency teams of impending risks or complications. The speed and clarity by which the young adult communicated with the community medical support teams was improved utilising WhatsApp® and smartphones. After a stable and adverse incident free six months of treatment, the young adult transitioned to a nocturnal home programme. Conclusion: A young adult can haemodialyse at home independently provided strategies are put in place to ensure the safety of the patient in the community.